ARJUNAWIWĀHA The marriage of Arjuna of Mpu Kanwa - Robson, Stuart (Bibliotheca Indonesica, 2008)
The Arjunawiwāha is one of the best known of the Old Javanese classics. This volume presents a new text, based on Balinese manuscripts, with a complete translation, building on the work done by earlier writers. An introduction provides ample background information, as well as an original interpretation of the significance of the text, within its historical and cultural setting. This poem was written by Mpu Kanwa in around A.D. 1030 under King Airlangga, who ruled in East Java. It is Mpu Kanwa's only known work, and is the second oldest example in the genre of kakawin. The poem is a narrative, but also contains passages of description, philosophical or religious teaching of great interest, as well as remarkable erotic scenes. Parts of the tale have been depicted on early temple reliefs and in paintings, and the text is still recited in Bali by literary clubs and in temple ceremonies. Stuart Robson, Associate Professor of Indonesian at Monash University from 1991 to 2001 and now retired, has been studying Old Javanese for more than forty years. He is interested in the problem of how to translate works of Old Javanese literature in such a way as to make these more accessible and better known to a wider audience of both scholars and general readers.